Answer:
As [tex]x[/tex] increases without bound, [tex]f(x)[/tex] increases without bound.
Step-by-step explanation:
[tex]Given\ f(x)=413x+3\\f(1)=413+3=416\\f(2)=413\times 2+3=829\\f(3)=413\times 3+3=1242\\.\\.\\.\\[/tex]
Hence with the increasing value of [tex]x[/tex], [tex]f(x)[/tex] increases.
[tex]x[/tex] can be any value between [tex]-\infty[/tex] to [tex]\infty[/tex] and [tex]f(x)[/tex] can have any value between [tex]-\infty[/tex] to [tex]\infty[/tex].
Hence as [tex]x[/tex] increases without bound, [tex]f(x)[/tex] increases without bound.
This can be seen from the graph attached(with the increasing value of [tex]x[/tex], [tex]f(x)[/tex] increases.